Ulcerated White Lesion of Tongue in a 7-Year-Old Child: A Diagnostic Dilemma - Shakya, Royasa; Koirala, Bandana; Dali, Mamta; Shrestha, Sneha (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Tongue is a complex organ associated with functions of taste, speech, mastication, deglutition, and development of jaws. It is considered the mirror of physical health as it can be the site of infections, immunological and drug-induced reactions, neoplasms and systemic diseases. This paper aims to present challenges in diagnosing a case of a 7-year-old male child who presented with ulceration and extensive white coating on the dorsum of tongue accompanied by fever, chills, tonsillitis, and submandibular lymphadenopathy. Despite symptomatic treatment done, the white coating with patches of depapillation lasted for a relatively long time. This may be the first reported case in the literature with such unusual tongue lesions in a child till date. Thus, pediatric dentists should have sound knowledge of the commonly encountered oral soft tissue lesions along with the rarer lesions and unusual presentation of common lesions for timely diagnosis, appropriate treatment, and referral if necessary.